COVID-19 and Chinese stock prices: a volatility analysis - Suixin, Gao (2024)
The 2020-2023 COVID-19 pandemic is the longest lasting and most extensive public emergency since the founding of China. In order to explore the impact of such public emergencies on China's economy, this paper proposes a hypothesis: the COVID-19 pandemic will cause fluctuations in the stock market and affect the economy. In order to explore the short-term impact of the COVID-19 outbreak on the Chinese stock market, this paper uses GARCH (1,1) to study the volatility changes of the Shanghai Stock Exchange Composite Stock Index (SSEC) and the Growth Enterprise 50 Index (SZEXT50) from 2020 to 2023.